Digital Post-Purchase Blues to Strategic Insights: A Bibliometrics-Based Systematic Review of Customer Purchase Regret - Zaheer, Asma (British Journal of Marketing Studies, 2024)
Deciphering the trends and evolutionary paths of the research on customers’ post-purchase regret inside the business milieu is crucial for marketing research and application. The current study in-tends to present a succinct bibliometric review based on synthesising the research on customers’ regret. We followed a systematic, sequential and objective process to retrieve a literature corpus comprising 204 peer-reviewed articles from the Scopus database. The literature corpus was cleaned first and then analysed using statistics-based techniques such as descriptive analysis, co-citation network analysis and keyword co-occurrence analysis. The analyses revealed (1) performance, revealing the most productive constituents and trends of the domain and (2) science of the domain, resulting in five thematic clusters representing the domain’s intellectual structure: purchase decision and sales, decision-making and regret, post-purchase regret, and anticipated regret. This study provides crucial insights and presents an agenda for research for future marketing scholars by comparing the recent advancements in the literature on consumerism with those in the wider marketing management literature.